Recognition of avirulence gene AvrLm1 from hemibiotrophic ascomycete Leptosphaeria maculans triggers salicylic acid and ethylene signaling in Brassica napus - Sašek, Vladimír; Nováková, Miroslava; Jindřichová, Barbora; Bóka, Károly; Valentová, Olga; Burketová, Lenka (Molecular plant-microbe interactions, 2012)
Interaction of a plant with a fungal pathogen is an encounter with hundreds of molecules. In contrast to this, a single molecule often decides between the disease and resistance. In the present article, we describe the defense responses triggered by AvrLm1, an avirulence gene from a hemibiotrophic ascomycete, Leptosphaeria maculans, responsible for an incompatible interaction with Brassica napus. Using multiple hormone quantification and expression analysis of defense-related genes, we investigated signaling events in Rlm1 plants infected with two sister isolates of L. maculans differentiated by the presence or absence of AvrLm1. Infection with the isolate carrying AvrLm1 increased the biosynthesis of salicylic acid (SA) and induced expression of the SA-associated genes ICS1, WRKY70, and PR-1, a feature characteristic of responses to biotrophic pathogens and resistance gene-mediated resistance. In addition to SA-signaling elements, we also observed the induction of ASC2a, HEL, and CHI genes associated with ethylene (ET) signaling. Pharmacological experiments confirmed the positive roles of SA and ET in mediating resistance to L. maculans. The unusual cooperation of SA and ET signaling might be a response to the hemibiotrophic nature of L. maculans. Our results also demonstrate the profound difference between the natural host B. napus and the model plant Arabidopsis in their response to L. maculans infection.
Keywords: Salicylic Acid; ethyleny; Plant Diseases; Ethylenes; regulace genové exprese u hub; časové faktory; Signal Transduction; Ascomycota; Time Factors; nemoci rostlin; Brassica napus; signální transdukce; Fungal Proteins; Plant Leaves; fungální proteiny; listy rostlin; kyselina salicylová; Gene Expression Regulation, Fungal